Perspectives of Social Capital and Self-Determination on e-WOM at Millennial Generation in Yogyakarta - Astuti, Budi Astuti; Hariyawan, Afif (Universitas Bangka Belitung, 2021)
Technological developments triggered the emergence of social media which continues to develop rapidly. This development is in line with the increasing number of social media users. This results in more and more customers making purchasing decisions according to social media references. Thus, social networking based communication becomes a necessity for companies to remain competitive. The purpose of this study is to examine the impact of social capital and self-determination on e-WOM in the context of social networking. The social capital factor is tie strength, shared language and trust, while the self-determination factor is self-disclosure and innovation. Surveys were conducted on 204 millennial generation respondents who had used social media in shopping in Yogyakarta. The results of the SEM analysis show: the tie strength and shared language influences trust. Likewise, there is an effect of the tie strength on shared language. In addition, there is an influence between trust, tie strength and self-disclosure towards e-WOM. Whereas, shared language and innovation have no effect on e-WOM. Thus to be effective in communication strategies through e-WOM, marketers can prioritize increasing the strength of relationships between members of social networks.